Políticas públicas, emergencia sanitaria y calidad de vida de la población de la provincia de Loja (Ecuador) - Moreno, Alex (2024)
The global pandemic that occurred generated a health, political, economic and social crisis; for this reason, we sought to identify the Impact of Public Policies and the Health Emergency on the Quality of Life of the population of Loja-Ecuador. An applied research with a quantitative approach was carried out on a sample of 384 people. It was determined that occasionally the government establishes favorable Public Policies for Ecuadorians; that prevention measures sporadically favored health control; that vaccination allowed the mitigation of the negative impact of COVID-19 on health; and, that most of the Quality of Life conditions remain the same; except for those of physical and personal security, which have worsened. It is concluded that the Health Emergency has had a significant impact on the Quality of Life; and, that the combination of Public Policies and the Health Emergency have had a moderate impact on the Quality of Life variable.